ประสิทธิผลและความปลอดภัยของการใช้ยาเม็ดมะขามแขกในการรักษาภาวะท้องผูกเรื้อรังในผู้ป่วยไตวายระยะสุดท้าย - นงลักษณ์ ลิ้มกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This before and after study was designed to assess the effectiveness and safety of senna tablets for the treatment of chronic constipation in patients with end stage renal disease (ESRD) undergoing hemodialysis (HD) or continuous ambulatory peritoneal dialysis (CAPD) at Phramongkutklao Hospital. Initially 51 patients were included. Data from 48 patients was used for analysis (22 men, 26 women; mean age 59.5 ± 13.8 years). Patients were treated with 2 tablets of senna once daily at bedtime for one week. The dose was increased by 2 tablets per day each week until approaching the maximum dose (8 tab per day) in the patients who had no response during the preceding one week, then continue of with this dose for 4 weeks. The results showed that the response rate was 87.5 % and statistically increase the defecation frequency per week from 1.0 ± 1.0 to 6.1 ± 1.8 (p < 0.001). The average daily dosage for this group of patients was 3.2 ± 1.4 tablets. Adverse effect such as flatus, griping, abdominal pain and loose stools occurred during study. However, one patient reported severe abdominal pain during senna tablet therapy, the symptoms disappeared after discontinue the medicine. No clinically significant differences in blood chemistries were observed during enrollment and the active treatment period. From this study showed that senna tablet is effective and safe to use in end stage renal disease patients. However, some patients cannot tolerate the adverse effects.